Should a Human Right Discourse be Applied to Labour Standards? - Shirzad, Morteza; Soltani, Sedighe (European Journal of Social Science Education and Research, 2022)
Whether a rights discourse should be applied to labour standards, entails addressing two issues. Firstly, what are the philosophical grounds for labour rights and whether they are human rights at all? Even if they cannot be regarded as human rights, should they be applied strategically? While, there is no single comprehensive theory identified to provide sufficient grounding for all labour rights, this paper argues, firstly, that labour rights certainly lack characteristics of universal human rights since they are time-bound and place-bound. Secondly, while recognising the relatively large strategic turn to human rights discourse by labour scholars and labour organisations, this paper argues that this is not a universally applicable strategy and in fact in some contexts application of human rights discourse is counterproductive. The paper, thus, concludes that not only deploying human rights approaches when it comes to countries authoritarian contexts are not effective, but also it is highly likely to be counterproductive, since human rights discourse needs public rights awareness public and authoritarian contexts lack this awareness.
Keywords: Labour rights, Human Rights and Human Rights Discourse